Establishment of a Highly Efficient In Vitro Regeneration System for Nandina domestica ‘Firepower’ - Xin Zhao; Hao Dong; Yanhua Li; Xinxin Zhang; Yajing Ning; Chengpeng Cui; Shujuan Li (Plants)
Nandina domestica ‘Firepower’ is one of the most popular colorful foliage species in landscaping. However, it is currently propagated mainly by seeding and cuttings, with a low reproduction coefficient, hindering the cultivation of this species. Therefore, establishing an in vitro regeneration system would be beneficial for the industrialized production of Nandina domestica ‘Firepower’. In this study, an ex vivo regeneration system was established using the direct organogenesis pathway. In early April, the new shoots of Nandina domestica ‘Firepower’ were selected, and the stem segments of 1~2 cm were cut as the disinfection materials for the explants. The optimal formulation for inducing axillary shoots was 1/2 MS + 1.5 mg L−1 6-benzylaminopurine (BA) + 0.3 mg L−1 indole-3-butric acid (IBA). The optimal formulation for the differentiation and proliferation of axillary shoots was 1/2 MS + 1.5 mg L−1 BA + 0.01 mg L−1 IBA with a multiplicity of proliferation of 9.22. We determined that the rooting of axillary shoots required a combination of IBA, naphthalene acetic acid (NAA), and activated carbon (AC). The optimal formulation for rooting was 1/2 MS + 0.2 mg L−1 NAA + 0.3 mg L−1 IBA + 0.2 mg L−1 AC. After a two-day hardening period for tissue-cultured plantlets, a substrate consisting of peat soil, vermiculite, and perlite at a ratio of 2:2:1 was determined to be the optimal cultivation formulation. This system provides a framework for the industrialized production of Nandina domestica ‘Firepower’.